Functional performance tests identify lateral ankle sprain risk: A prospective pilot study in adolescent soccer players - Ko, J.; Rosen, A.; Brown, C. N. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Determining the clinical utility of functional performance tests (FPTs) and establishing cutoff scores could be useful in identifying those athletes who could benefit from effective injury prevention interventions. Our purpose was to determine the accuracy of FPTs in identifying adolescent athletes who go on to experience lateral ankle sprain(s) and establish specific cutoff scores capable of identifying those who sustain a lateral ankle sprain in the near future. Sixty-four participants (age = 15.5 ± 1.3yrs; height = 161.7 ± 7.7cm; mass = 57.1 ± 8.4kg) were recruited from a junior soccer club and tracked for 10 months. Participants performed the anterior (AN), posterior-medial (PM), and posterior-lateral (PL) reach directions of the Star Excursion Balance Test (SEBT) and the Single-Leg Hop Test (SLHT) in pre-season, and then were followed for the 10-month competitive season (12 injured, 52 uninjured). Significant Area Under the Curve (AUC) values and cutoff scores were found for the PM (AUC=0.78; 95% CI 0.61-0.95; p=0.003; Sn=0.83; Sp=0.77; cutoff=76%) and the PL (AUC=0.82; 95% CI 0.71-0.94; p=0.001; Sn=0.92; Sp=0.65; cutoff=70%) reach directions of the SEBT and the SLHT (AUC=0.77; 95% CI 0.60-0.95; p=0.003; Sn=0.67; Sp=0.94; cutoff=15.4sec). The PM and PL reach directions of the SEBT and the SLHT may be useful as pre-season screening measures to help clinicians identify adolescents who will go on to experience a lateral ankle sprain.